Patient experience with pharmaceutical care: a systematic review of service users’ experience with pharmacist-led services in ambulatory care - Vanessa Klimkowski Argoud; Carine Raquel Blatt; Sophia Gluer Normann; Gabriel Ricardo Fernandes; Matheus de Matos Medina; Marcelo Pedrotti Barbieri; Nicole Schons Jung; Mellina da Silva Terres (International Journal of Pharmacy Practice, 2026)
Abstract Objectives To examine how patient experience (PX) has been defined, assessed, and reported in pharmacist-led services delivered in ambulatory care, and to identify experiential themes across service models. Methods A systematic review was conducted and registered in PROSPERO (CRD42025635268), and the results were reported according to PRISMA 2020. MEDLINE (Ovid), Embase, and LILACS were searched from 1 January 2000 to 31 December 2024. Interventional and observational studies examining service users’ experiences with pharmacist-led ambulatory services beyond satisfaction measures were included. Inpatient and non–pharmacist-led services were excluded. Titles, abstracts, and full texts were independently screened by two reviewers, and data were extracted independently. Methodological quality was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist for Qualitative Research, and confidence in findings was evaluated using GRADE-CERQual. Given the heterogeneity, a narrative synthesis was conducted, guided by a multidimensional experiential framework. Key findings Twenty-three studies were included, predominantly qualitative (n = 18) and conducted in high-income countries (n = 22). Only two studies explicitly defined PX, and two used validated Patient-Reported Experience Measures. Three recurring themes were identified: trust (n = 18), accessibility (n = 14), and holistic and longitudinal care (n = 12). In-person services emphasized relational continuity, remote services prioritized convenience but raised concerns about impersonality, and hybrid models combined flexibility with continuity. Confidence in the review findings was high for trust, moderate for accessibility, and low to moderate for holistic and longitudinal care. Conclusions PX in pharmacist-led ambulatory services is multidimensional yet inconsistently conceptualized and measured. Clearer operationalization and routine assessment may strengthen service evaluation and support sustainable implementation.